Forging A New Nation: The Role of Youth Radicalism in Semarang’s Revolutionary Struggle, 1945-1947 - Dwi Mulyatari; Abdurakhman; Raisye Soleh Haghia; Syahidah Sumayyah Rahman (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: This study examines the youth resistance movement in Semarang in the early days of the Indonesian Revolution, especially between 1945 and 1947, against the Japanese and Allied armies. The youth resistance movement is characterized by a militant and radical nature, which is influenced by various factors from the past experiences of the youth. In addition to the impact of the Japanese occupation, ideological factors such as Socialism, Communism, Islam, and Nationalism also played an important role in encouraging youth radicalism in Semarang. Research on the radical youth movement in Semarang during the Indonesian Revolution is still limited, with some studies highlighting events such as the 'Five-Day Battle'. This research contributes to the understanding of the youth militant movement in Semarang through a literature review from contemporary newspaper sources published in Jakarta and Semarang as well as other related literature collections. These sources are obtained from the National Library and libraries in the local area. The results of the study show that several factors affect radicalism and youth militancy in Semarang. First, their strong motivation and purpose to resist the occupation of the Japanese army and the return of the Allies. Second, the results of Japanese education for youth through military and semi-military organizations during the Japanese occupation that strengthened the military mentality. Third, the influence of the socialist-Marxist youth group organization that developed since the time of the national movement, thus making the city of Semarang known as a